An evidence-based algorithm for early prognosis of severe dengue in the outpatient setting. - Nguyen, MT; Simmons, Cameron; Ho, TN; Nguyen, VVC; Nguyen, TH; Ha, MT; Ta, VT; Nguyen, LDH; Phan, L; Han, KQ; Duong, THK; Tran, NBC; et al. (2018)
BACKGROUND: Early prediction of severe dengue could significantly assist patient triage and case management METHODS: We prospectively investigated 7563 children with ≤3 days of fever recruited in the outpatient departments of six hospitals in southern Vietnam between 2010 and 2013. The primary endpoint of interest was severe dengue (2009 WHO Guidelines) and pre-defined risk variables were collected at the time of enrolment to enable prognostic model development. RESULTS: The analysis population comprised 7544 patients, of whom 2060 (27.3%) had laboratory-confirmed dengue and nested amongst these were 117 (1.5%) severe cases. In the multivariate logistic model a history of vomiting, lower platelet count, elevated aspartate aminotransferase (AST), positivity in the NS1 rapid test and viremia magnitude were all independently associated with severe dengue. The final prognostic model (Early Severe Dengue identifier- ESDI) included history of vomiting, platelet count, AST level and NS1 rapid test status. CONCLUSIONS: The ESDI had acceptable performance features (AUC=ΓÇë0.95, sensitivity 87% (95%CI: 80-92%), specificity 88% (95%CI: 87-89%), positive predictive value 10% (95%CI: 9-12%), negative predictive value of 99.8% (95%CI: 99.6-99.9%)) in the population of all 7563 enrolled children. A score-chart, for routine clinical use, was derived from the prognostic model and could improve triage and management of children presenting with fever in dengue endemic areas.